Enforcing dust mass conservation in 3D simulations of tightly coupled grains with the Phantom SPH code. Issue 2 (16th March 2018) - Ballabio, G; Dipierro, G; Veronesi, B; Lodato, G; Hutchison, M; Laibe, G; Price, D J
Abstract: We describe a new implementation of the one-fluid method in the SPH code Phantom to simulate the dynamics of dust grains in gas protoplanetary discs. We revise and extend previously developed algorithms by computing the evolution of a new fluid quantity that produces a more accurate and numerically controlled evolution of the dust dynamics. Moreover, by limiting the stopping time of uncoupled grains that violate the assumptions of the terminal velocity approximation, we avoid fatal numerical errors in mass conservation. We test and validate our new algorithm by running 3D SPH simulations of a large range of disc models with tightly and marginally coupled grains.